Solar UAV : structural dynamic analysis of critical components - Tan, Genial Aik Ruey. (2013)
This thesis provides a detailed outline of the author’s final year project in Nanyang Technological University, School of Mechanical and Aerospace Engineering. This project consists of constructing a solar powered Unmanned Aerial Vehicle (UAV) with the requirements of Medium Altitude Long Endurance (MALE). The end objective of this project is for the Solar UAV to be able to maintain non-stop flight for 24 hours. With a team of ten final year students, the author seeks to design and construct the UAV, with sub-teams such as aerodynamics, structures, solar, avionics and propulsion. Being part of the structures team, the main role of the author is to conduct structural analysis on all the components of the plane using FEM software. As this is a large scale project that will span over another approximately two years, the author has included an abbreviated manual on how to use a FEM software, ABAQUS, in the FYP report.